ANALISIS PENGARUH FUNDAMENTAL DAN MAKRO EKONOMI TERHADAP KEBIJAKAN DIVIDEN DENGAN RETURN ON ASSET SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2015 - Chandra, Ade; Efni, Yulia; Emrinaldi, Emrinaldi (Jurnal Tepak Manajemen Bisnis, 2018)
The purpose of this study is to prove empirically the influence of cashpositition, debt to equity ratio, BI interest rate, inflation, exchange rate and GrossDomestic Product on dividend policy. And to prove empirically the influence ofReturn on Asset on dividend policy, the influence of cash positition, debt to equityratio, BI interest rate, inflation, exchange rate and Gross Domestic Productthrough return on asset to dividend policy. The population of this research is allcompanies engaged in manufacturing industries that go public in Indonesia StockExchange in 2012 until 2015 as many as 168 companies. To determine sample isusing purposive sampling method. The sample that meets the criteria there are 43companies. To analyse data is using path analysis method. The results show thatcash position has a significant influence on dividen policy (DPR) in addition tothe cash position also affect the dividen policy through ROA. Debt to equity rationegatively affects dividen policy. Debt tot Equity Ratio affects dividen policythrough ROA. Interest rates have no significant effect on dividen policy. Interestrates also have no effect on dividen policy through ROA. Inflation affects dividenpolicy but does not affect dividen policy through ROA. Exchange rate does notaffect dividen policy. The exchange rate does not indirectly affect the dividenpolicy through ROA. Gross domestic product has an influence on dividen policy.Gross domestic product indirectly affects the dividen policy through ROA.